المسؤولية الاجتماعية ودورها في مساهمة القطاع الخاص في التنمية المستدامة - غدير إبراهيم, ظريفة (University of eloued جامعة الوادي, 2019)
هتدده هدلد الدراسدة عر اللىدده تلدم مدد لندع مخلسصدوال الالدوي افدو لسؤودة الدسا دس ا صدخل ل ة اؤجلموت دةو اللىدده تلدم لدسؤواال ا صدخل ل ة اؤجلموت دة تلدم الالدوي افدو م ا ده ل م دة مصدلدامة لمى دوو ح دح ح دل مدا مخلسصدوال الالدوي افدو صدخل ل ل و اؤجلموت دة موهلمدو الدو م الصد ساال انهدو ر د ا د ل س مونمد اجلدودو ذلك لنىدو للللدسراال اصوةدلة م ال دد ه اؤدلةدو وة اؤجلموت دة م الىدوا م ىدا الىس دة مد ج ة لألفمور اليت جوء هبو ال مد اؤدلةدو الدل ودد اه اهدداه ا خلسصدة لددلنا مسهدداه ا لمد الدل لىمدا مد مد ج دة اهدد ل هدة او دة هدلا ا سددسي خللدا امىدو د الديت حدو ع الميدو راسدل و حةددهو مد ل ده ا خلسصوال افوةة تلم لن و م اجا السةسع عر ل م ة مصلدامة لادد اتلمددال الدراسدة تلدم ا د جل السةد ل م اجلو دل ال دد و ا د جل الل ل لدل اؤسدلدؤ م اجلو دل الللن ادل م د و موؤتلمدو تلدم اسدلسم ا صدمت اؤجلمدوتلو ا اسدلخدا ا ا اؤسدلن وه ىدفدة راء ت دة الدراسدة ا مس دة مد 04 مد تمدوع هبدلد ا خلسصدوالو ا ل دا ال لدوججل تلدم مد دومجل اصلمدة اتحةدوج ة للىلدس اؤجلموت دة SPSS Amos SPSSو ا اهلنور ال لوججل الدراسة موسلىموع اسول ل عحةوج ة ميا: اؤهلندوراال النىدودة م حولة جس فد ق ذاال ؤلة عحةوج ة لسةددل و اه مخلسصددوال الالددوي افددو م ؤوددة الددسا ؤ لصددوه م ل م ددة علمى ددو ا لددلو لدد اص م ل سودد اسليموراهتو ددد ا ةدد الدراسدة متدد ر لست دة مخلسصدوال الالدوي افدو مدد رهو م مدا مصدخل ل ل و تدس علمى دوو تد طدوده تد ان دلة اؤجلموت دة لسج د مىد اسدليموراهتو ذاال ةدنمة اجلموت دة لصدوه م لدسفو فدد الىمدا دو وصوه م حد م النلولة موللو ل م ة مج اجلسا ل الل م ة stract: This study aims to identify the extent to which the private sector institutions in El oued state adopted the concept of social responsibility, And to identify the impact of social responsibility on the private sector in achieving sustainable development of society, Where private sector institutions have taken on greater social responsibility in recent years, although it is not new, Depending on the developments in the economic and social conditions in the world due to globalization on the one hand and the ideas that came from the economic thought, which believes that the objectives of the institution are linked to the objectives of the society in which it works on the other hand, As a result of the importance of this subject in various dimensions, which has been much studied and limited, while encouraging private institutions to adopt them in order to achieve sustainable development. The study was based on the descriptive approach on the theoretical side and the inference analytical approach in the applied side,Drawing on the social survey method, The survey was used to find the views of the sample of the study consisting of 40 workers in these institutions, The results were analyzed on the statistical package program for social sciences (SPSS), The results were tested using statistical methods such as: Post-tests in the case of statistically significant differences. We found that the private sector institutions in El oued state do not contribute to the development of their local community, due to the lack of diversification of their investments, The study recommended that the private sector institutions should be made aware of their role in assuming responsibility towards their society, By supporting social activities and directing some of their investments of a social nature contribute to the provision of employment opportunities, which contributes to reducing unemployment and thus development of all aspects of development. key words: Social responsibility, private sector institutions, sustainable develop الكلمات المفتاحية: ا صخل ل ة اؤجلموت ةو مخلسصوال الالوي افو و الل م ة ا صلدامة
مذكرة ماستر تخصص مالية وتجارة دولية
Keywords: ومؤسسات القطاع الخاص ، والتنمية المستدامة; Social responsibility, private sector institutions, sustainable develop